2012
DOI: 10.1002/stem.775
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Requirement for Notch Signaling in Maintenance of the Quiescent Skeletal Muscle Stem Cell State

Abstract: Notch signaling plays a key role in virtually all tissues and organs in metazoans; however, limited examples are available for the regulatory role of this pathway in adult quiescent stem cells. We performed a temporal and onto-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
448
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 432 publications
(482 citation statements)
references
References 40 publications
30
448
2
2
Order By: Relevance
“…Inhibition of the Notch signaling in satellite cells, as well as the deficiency of Ten‐4 as shown in this study, forces to exit the quiescent state 13, 14, 15. Brohl et al reported that the Ten‐4 expression level was significantly reduced in the double knockout mice of RBP‐J and MyoD, where Notch signaling was deactivated.…”
Section: Discussionsupporting
confidence: 54%
“…Inhibition of the Notch signaling in satellite cells, as well as the deficiency of Ten‐4 as shown in this study, forces to exit the quiescent state 13, 14, 15. Brohl et al reported that the Ten‐4 expression level was significantly reduced in the double knockout mice of RBP‐J and MyoD, where Notch signaling was deactivated.…”
Section: Discussionsupporting
confidence: 54%
“…However, the effect of depletion of CD9P-1 is unlikely to be a consequence of altered Notch signalling as we observed no significant change in the expression of Notch targets, hes-1 and hey-1 ( Supplementary Fig. S4g), that have been demonstrated to be under the control of Notch in adult myogenic progenitors 44 . The precise mechanisms through which CD9P-1 regulates muscle cells fusion will require further investigations.…”
Section: Discussionmentioning
confidence: 67%
“…[6][7][8][9][10][11] The expression of Hes1 induced by Notch can be detected more than embryo neural stem cells, intestinal crypt progenitor cells, pancreatic stem cells, bone marrow mesenchymal progenitors and quiescent skeletal muscle stem cells. 9,10,[68][69][70][71] Treatment with g-secretase inhibitor (GSI) results in the suppression of Hes1 and the differentiating state of those stem cells, indicating the role of the Notch pathway in Hes1 expression, as well as the essential status of the Notch-Hes1 pathway in facilitating cell fate decisions and regulating differentiation during development.…”
Section: Canonical Notch Signaling Pathwaymentioning
confidence: 99%